2006
DOI: 10.1021/ac060513+
|View full text |Cite
|
Sign up to set email alerts
|

Using Capillary Electrophoresis−Selective Tandem Mass Spectrometry To Identify Pathogens in Clinical Samples

Abstract: Analysis of microbial mixtures in complex systems, such as clinical samples, using mass spectrometry can be challenging because the specimens may contain mixtures of several pathogens or both pathogens and nonpathogens. We have successfully applied capillary electrophoresis-selective MS/MS of unique peptide marker ions to the identification of common pathogens in clinical diagnosis. We searched the CE-MS/MS spectra acquired from the proteolytic digests of pure bacterial cell extracts against protein databases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Other groups have directed their attention to the identification of microorganisms by means of peptide analysis of the proteins derived from them [53,73], demonstrating that CE-MS can also be used to identify different microorganisms present in different matrices even in low amount. Besides, Erny and Cifuentes [103] developed a CE-MS mapping approach to obtain 2-D maps of protein digests that allowed easy and simultaneous visual inspection of large dataset as well as to observe immediately relevant differences in closely related samples.…”
Section: Ce-ms Using Bare Fused-silica Capillariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other groups have directed their attention to the identification of microorganisms by means of peptide analysis of the proteins derived from them [53,73], demonstrating that CE-MS can also be used to identify different microorganisms present in different matrices even in low amount. Besides, Erny and Cifuentes [103] developed a CE-MS mapping approach to obtain 2-D maps of protein digests that allowed easy and simultaneous visual inspection of large dataset as well as to observe immediately relevant differences in closely related samples.…”
Section: Ce-ms Using Bare Fused-silica Capillariesmentioning
confidence: 99%
“…the electroosmotic flow, these neutral coatings are usually employed in CE-MS using a sheath flow interface, since, as already mentioned above, this interface is less dependant on the EOF. For instance, linear polyacrylamide has been used as coating for peptide analysis by CE-MS [67], as well as poly(vinyl alcohol) (PVA) [37,57,73,85] demonstrating its suitability to prevent peptides adsorption during the analysis of these molecules. In fact, Hu et al [73] showed that it was possible to identify using PVA-coated capillaries and CE-MS/ MS, common pathogen microorganisms in clinical diag- nosis by means of the selective identification of some of their specific peptides selected as biomarkers.…”
Section: Ce-ms Using Coated Capillariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the application of this approach to food analysis presents some difficulties due to inherent variability of cellular composition of bacteria under different environmental conditions. To overcome the problem of poor identification induced by limited mass accuracy in the determination of relative molecular mass of proteins when using low resolution MS analyzers, Hu et al [78,79] applied CE-MS/MS to selected peptide ions to obtain partial sequences of protein biomarkers. The coupling CE-MS/MS can provide a highly selective and sensitive analytical method for characterizing the analytes present in complex mixtures.…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…Proteins that have been extracted from microbial samples can be digested by enzymes; the sequence information of the peptides, obtained by MS/MS, can then be utilized to identify the proteins and deduce the microorganism's source through a proteome database search [23][24][25][26][27][28][29][30]. Recently, the authors' group reported approaches that use the selective proteotypic-peptide analysis (SPA) of protein digests that have been separated through CE to accurately identify bacterial mixtures [31][32][33]. Proteotypic peptides refer to those experimentally observable peptides that identify specific proteins [34].…”
mentioning
confidence: 99%